Prevalencia de leptospirosis en cerdos y factores de riesgo en la población animal y humana del cantón Portoviejo, provincia de Manabí - Guerrero Santana, María Victoria (2019)
The objective was to determine the prevalence of swine leptospirosis and its association with risk factors in the animal and human population in Portoviejo canton, province of Manabí. The research is divided into two stages, the non-experimental one, surveys are carried out in five parishes, in Portoviejo canton (Portoviejo, Alajuela, Abdón Calderón, Riochico and San Plácido), it is considered the breeding system (farms and backyard). While the experimental stage consisted of taking blood samples in breeders and stallions, in the same parishes. The results of the agreement on the serovars detected in the farms were Australis (19.59%), Canicola (17.53%) and Bataviae (14.43%), and in backyards they were Icteroahemorragiae (18.88%), Canicola (16.78%), and Bataviae (16.08%). On the other hand, for the diagnosis of Leptospira spp., through the survey of risk personnel and members of the sector under study, it was found that a large percentage of citizens do not handle biosafety and health control standards in both parenting systems. In the risk analysis in farms and backyard with respect to seropositivity to leptospirosis, specific differences were found for vaccination against leptospirosis in the farm (P = 0.01), female sex in backyard (P = 0.03), and for the rainy period (P = 0.00). It is concluded that for the diagnosis of leptospirosis it is necessary to include a causal analysis of multiple clinical situations, in order to obtain a diagnosis of the pathology.